2015
DOI: 10.1523/jneurosci.1666-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dysregulation of Hippocampal Inhibition in the Mouse Lacking Autism Candidate GeneCNTNAP2

Abstract: Mutations in the human gene encoding contactin-associated protein-like 2 (CNTNAP2) have been strongly associated with autism spectrum disorders (ASDs). Cntnap2 ؊/؊ mice recapitulate major features of ASD, including social impairment, reduced vocalizations, and repetitive behavior. In addition, Cntnap2 ؊/؊ mice show reduced cortical neuronal synchrony and develop spontaneous seizures throughout adulthood. As suggested for other forms of ASDs, this phenotype could reflect some form of synaptic dysregulation. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 28 publications
4
64
0
Order By: Relevance
“…In this condition, a 90% reduction in LH4 expression was observed in hippocampi expressing two distinct sgRNAs against LH4 (sgLH4-1 and -2) (Figure S4A). To examine eIPSCs, we placed a stimulating pipette in the middle of the stratum pyramidale 150 μm away from the recorded cell (Jurgensen and Castillo, 2015). IPSCs were elicited upon stimulation and the eIPSC amplitude was saturated at 24 μA in CA1 neurons expressing sgLH4-1 (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…In this condition, a 90% reduction in LH4 expression was observed in hippocampi expressing two distinct sgRNAs against LH4 (sgLH4-1 and -2) (Figure S4A). To examine eIPSCs, we placed a stimulating pipette in the middle of the stratum pyramidale 150 μm away from the recorded cell (Jurgensen and Castillo, 2015). IPSCs were elicited upon stimulation and the eIPSC amplitude was saturated at 24 μA in CA1 neurons expressing sgLH4-1 (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies are required to explore whether E:I imbalance in other brain regions, such as sensory associative areas, striatum, and hippocampus (44), may be involved in the emergence of behavioral phenotypes in the CNTNAP2 KO mice and whether similar pathophysiological mechanisms occur in other genetic models of autism. These studies will be critical to form a unified mechanistic and translational understanding of the neurons and circuits that underlie autism spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This rodent model is characterized by asynchronous cortical neuronal firing, as well as a strong reduction in the number of GABAergic INs in the somatosensory cortex and striatum (with a highest reduction in the PV+ subtype). Furthermore, it has been shown that knockout of this gene affects spine density, glutamatergic receptor trafficking and perisomatic inhibition [73, 74]. In this sense, the pharmacological model of ASD based on prenatal exposure to valproate also showed a reduction of PV at the levels of protein, mRNA and cell number [75].…”
Section: Pre-clinical Models Of Asd and Ts With Interneuronal Alteratmentioning
confidence: 99%